Comparision of various models for calculation of reference evapotranspiration with reference to Penmann-Montieth equation - Kumar, Vinay; Khan, Shafat (Indian Journal of Hill Farming, 2019)
Studies have evaluated and compared various popular empirical  apotranspirationequations that belonged to three categories: (1) mass-transfer based methods, (2) radiation based methods, and (3) temperature-based methods; and the best and worst equations of each category were determined for the study regions. In this study a comparison of the best  or representative equation forms selected from each category was made from the FAO-56 Penman-Monteith model using data given at the required station Daily and monthly output from six evapotranspiration models (ASCE Standardised Evapotranspiration , FAO-24Blaney-Criddle, Hargreaves-Samani, Priestly-Taylor, Makkink, and FAO Pan Evaporation) have been tested against reference evapotranspiration data computed by the FAO- 56 Penman-Monteith model to assess the accuracy of each model in estimating grass reference evapotranspiration in an experimental field in Shalimar. A pan evaporation to reference evapotranspiration model (FAO-24 Pan Evaporation) was also tested against daily grass reference Evapotranspiration were evaluated and compared with the Penman-Monteithequation using daily meteorological data from the Skuast-k observatory field. Seven representative empirical potential evapotranspiration equations selected from the three categories, namely: Hargreaves and Blaney-Criddle (temperature-based), Makkink and Priestley-Taylor (radiation-based) and Pan Evaporation (mass-transfer-based). The calculations of the Penman-Monteith equation followed the procedure recommended by FAO (Allen et al., 1998). The comparison was first made using the original constant values involved in each empirical equation and then made using the recalibrated constant values.The study showed that the original constant values involved in each empirical equation worked quite well for the study region, except that the value of α = 1.26 in Priestley-Taylor was found to be too high and the Further examination of the performance resulted in the following rank of accuracy as compared with the Penman-Monteith estimates: and ASCE Standardised Evapotranspiration Priestley-Taylor and Makkink (Radiation-based), Hargreaves and Blaney-Criddle (temperature-based) and Pan Evaptranspiration and method.